PEZIZA FIMETI (PEZIZALES: PEZIZACEAE): NEW RECORD OF A CUP FUNGUS FROM NEPAL - Adhikari, M. K. (Ecoprint: An International Journal of Ecology, 2014)
Peziza fimeti (Fuckel) Seaver, a member of wild coprophilus cup fungi belonging to the family Pezizaceae, has been recently collected growing on cow dung at Bhanimandal, Lalitpur. This species is reported here as a new record from Nepal. DOI: http://dx.doi.org/10.3126/eco.v20i0.11328 Ecoprint: An International Journal of Ecology Vol. 20, 2013 Page : 37-39